Amino-functionalized Cu-MOF for efficient purification of methane from light hydrocarbons and excellent catalytic performance. Issue 5 (22nd March 2019) - Wang, Xia; Zhang, Xiurong; Zhang, Kai; Wang, Xiaokang; Wang, Yutong; Fan, Weidong; Dai, Fangna
Abstract : Amino-functionalized Cu-MOF for the efficient purification of methane from light hydrocarbons and excellent catalytic performance. Abstract : A 3D microporous MOF [Cu1.5 (BTB-NH2 )(H2 O)2 ]·6DMA·5H2 O (UPC-99 ) of the (2, 3, 4- c )-net novel topology type was successfully constructed by the amino-functionalized ligand and Cu(ii ) ions via a solvothermal method. Due to the presence of two channels with open Cu(ii ) sites and –NH2 groups, UPC-99 exhibits a high adsorption selectivity of 15.3 for CO2 /CH4 at 1 bar and 273 K. Remarkably, UPC-99 exhibits a significant adsorption difference in C3 H6 and C3 H8 relative to CH4 and shows a high separation selectivity for C3 light hydrocarbons relative to CH4 (496.7 for C3 H6 /CH4 and 410.5 for C3 H8 /CH4 at 273 K, 1 bar) by single-component gas sorption and selectivity calculations in IAST methods. Moreover, the presence of open Lewis acidic Cu(ii ) sites in the channels allowsUPC-99 to exhibit excellent catalytic performance in the catalytic cycloaddition reactions of CO2 with epoxides.